O alçamento vocálico em dois falares mineiros: o item lexical e o individuo - Fernando Antônio Pereira Lemos (2018)
This thesis analyses the raising of pretonic mid vowels in two dialectal areas from Minas Gerais: in Divinópolis, West-Center of Minas Gerais, and Grão-Mogol, North of Minas Gerais. At this research we adopt the theoretical methodological model of the Complex Systems Theory (OLIVEIRA, 2014, 2015, 2016). We also take into account the Theory of Linguistic Variation and Change (LABOV, 2008). We separately analyzethe lexical items with a high vowel at the next syllable and the lexical items without a high vowel at the next syllable. Our results allows us to determine that there is lexical performance at the studied vowel raise, either to the lexical items with a high vowel at the next syllable and to the lexical items without a high vowel at the next syllable. Our research aims the raising, however, we found evidence that the raising of a mid-lowvowel [] to a mid-high vowel [o] is in progress in both studied cities. In Grão Mogol this change shows the lost a characteristic Bahias accent. We also found evidence that the raising is in progress in Divinópolis and Grão-Mogol among items without a following high vowel.